Cetacean stranding records along the Shanghai–Zhejiang coastline in China: implications for distribution and conservation - Yuan, Jing; Gao, Yili; Wang, Nan; Jiang, Tianhua; Cheng, Zhaolong (Frontiers in Marine Science, 2025)
Cetacean ecology has been poorly studied in the Shanghai-Zhejiang waters of East China Sea, seriously hindering appropriate local conservation practices. Here stranding records from 1953 to 2023 around the Shanghai-Zhejiang waters were collated from literature, media, and social websites to clarify species composition and spatio-temporal variations of cetacean strandings. A total of 138 stranding records involving 197 individuals across 23 species were identified, comprising four Mysticeti and Odontoceti species. Cetacean stranding records occurred extensively along the Shanghai-Zhejiang coastline throughout the year and have grown swiftly since the 2000s. Narrow-ridged finless porpoise Neophocaena asiaeorientalis and common minke whale Balaenoptera acutorostrata were the most frequently stranded species. Over 84% of the stranding events involved only a single individual. Melon-headed whale Peponocephala electra predominated in mass stranding incidents. Spatially, the stranding reports showed a significant cluttering distribution pattern. Clustering of cetacean records occurred in the Yangtze River estuary, downstream region of Qiantang River, southeastern of Ningbo, and Oujiang River estuary. Seasonal analysis showed increased cetacean stranding events in spring, yet without a significant difference. Post-mortem examinations of stranded individuals showed that coastal fisheries and port activities were probably the dominant causes of local cetacean strandings. Standardizing cetacean stranding records, strengthening fisheries regulations, and rescue training programs are recommended to establish a dedicated cetacean stranding monitoring network, which is vital for cetacean conservation in this region.